Particle properties for suspension plasma spray. Issue 6 (29th July 2014) - Lijuan, Qian; Chu, Xianyu
Abstract : Purpose: – The purpose of this paper is to use comprehensive model to investigate the effects of particle physical properties on in-flight nano-particles behavior for the radio frequency suspension plasma spray. Design/methodology/approach: – In this paper, both the effects thermal properties of solvent and solid particle on the evolution of particle size, velocity and temperature are discussed. Besides, the numerical analysis is also conducted to investigate the influences of particle physical properties on the characteristic distributions of particles for poly-disperse cases. Findings: – Results show the thermal properties of solvent have critical effects on the discharged point of the solid particles, but little influence on the final particle velocity and size, as well as their distributions. The final state of particle temperature is mainly determined by the solid particle thermal properties, especially depending on the boiling point. Originality/value: – Most of the former studies took the experimental approaches and mainly focussed on the operating conditions effects. While beyond the operating conditions, the variety of particle physical and thermal properties also has strong effect on particle heating performance.